Marketing Strategy for Processed Nira Products in Timbuseng Village, Gowa Regency - Ninik Lantara; Andi Dorawati; St. Hatidja; Masmarulan; Hidayah (www.amertainstitute.com, 2025)
The Marketing Strategy Training for Processed Palm Sugar Products aims to enhance partners' knowledge and strengthen the capacity of business actors in marketing their products effectively and competitively. Processed palm sugar products, such as palm sugar, syrup, and fermented beverages, have significant market potential due to their natural composition and high nutritional value. However, many business actors face challenges, including a lack of understanding of modern marketing strategies, limited product innovation, and restricted market access. This training covers essential topics such as marketing fundamentals, branding strategies, digital marketing, product and packaging innovation, and distribution management. Participants learn how to build a strong brand, leverage social media and online marketplaces for promotion, and develop a structured marketing plan. Through an interactive approach, participants engage in simulations and group discussions to apply the knowledge they have acquired. The training results indicate an improvement in participants' understanding of marketing principles, their ability to innovate products, and their skills in utilizing digital technology to expand market reach. This initiative is expected to help business actors enhance the competitiveness of processed palm sugar products, broaden their marketing networks, and contribute to local economic growth.